IMPROVING EFFICIENCY AND COORDINATION IN RICE PRODUCTION: EVIDENCE FROM MULUR VILLAGE - Daning Kusumawardani; Muhammad Hassan Massaty (Universitas Muhammadiyah Bengkulu, 2026)
This research explores the application of a Management Information System (MIS) aimed at improving coordination, efficiency, and transparency in the Mulur rice production network situated in Sukoharjo, Central Java. Utilizing a descriptive qualitative methodology paired with quantitative analysis, the study engaged 15 participants, comprising farmers, cooperatives, mill operators, and distributors. The MIS encompasses modules for land management, harvest forecasting, inventory management, and distribution to support data-driven decision-making and traceability within the supply chain. Quantitative findings reveal a high level of user satisfaction (mean = 4.23), with particular strengths in usability (4.35) and data precision (4.29). Qualitative insights indicate enhanced workflow alignment, quicker information sharing, and improved coordination among stakeholders. Nonetheless, challenges remain, including inconsistent connectivity, insufficient training, and partial system integration. Stakeholders pointed out the necessity for mobile accessibility, ongoing capacity development, and improved infrastructure